Care Relationships, Social Capital and Well-Being in the Caregiving of Persons With Disabilities: Evidence From a Qualitative Study in Italy - Ferrucci, Fabio; Monteduro, Giuseppe (Italian Sociological Review, 2025)
This study examines the forms of caregiving directed toward persons with disabilities, focusing on the role of informal support relationships and the types of social capital mobilized by family caregivers. The objectives were to (a) understand how care relationships are configured in everyday life, their meanings, and their effects on caregivers’ lives; (b) identify the role and functions of the reference person -the person who helps the caregiver the mostithin support networks; and (c) explore how bonding and bridging social capital influence caregiving practices and caregivers’ well-being. A mixed-methods design was adopted, consisting of 30 dyadic interviews with caregiver–reference person pairs, combined with Personal Network Analysis to map personal support networks. The interviews explored emotional and material challenges, meanings attributed to caregiving, access to social and health services, and representations of the future. Transcripts were analyzed through thematic coding, while Personal Network Analysis assessed network size, density, and alter attributes. Findings indicate that caregiving often takes the form of “perpetual parents” – a totalizing, continuous, and pervasive relationship that reshapes caregivers’ biographies and limits opportunities for employment, social participation, and self-determination. While participants reported prolonged stress, social isolation, and professional sacrifices, they also described emotional recognition and symbolic gratification. Care networks were predominantly characterized by familial bonding social capital, with bridging capital playing a crucial yet less developed role. The study underscores the centrality of informal networks in sustaining caregiving in Italy and highlights the need to strengthen community-based supports and public infrastructures to ensure continuity of care and enhance both caregiver well-being and autonomy for persons with disabilities.